REDISCOVERING LIFE'S CYCLES: EXPLORING THE MEANING OF NUNAKKISHU IN Q.S. YĀSĪN VERSE 68 - Qomariah Nur Mujahidah; Ahmad Nurrohim (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir)
This study delves into the concept of nunakkishu in Q.S. Yāsīn verse 68, which reflects the cyclical nature of human life—from the vulnerability of infancy, the strength of adulthood, to the eventual return to a weakened state in old age. By integrating Quranic exegesis with contemporary scientific perspectives on aging, cognitive decline, and Erik Erikson's psychosocial development theory, this research provides a comprehensive understanding of biological and psychological regression in later life. Utilizing a qualitative library research method, the study examines classical and contemporary interpretations of the verse alongside modern findings on aging. The results reveal that the term nunakkishu embodies not only the physical and cognitive transformations of aging but also serves as a profound reminder of human dependence on the Creator. Furthermore, it underscores the ethical and social dimensions of caregiving for the elderly, rooted in the Quranic values of compassion, respect, and social responsibility. This study contributes to a deeper understanding of life's cycles, offering recommendations to foster empathy and holistic care for the elderly, encompassing their spiritual, physical, and psychological needs.